Marcel-Lenoir et la fresque - Marie-Ange Namy (In Situ)
In the artistic landscape of the late nineteenth and the first half of the twentieth century, Marcel-Lenoir (1872-1931) included in the rewriting of the history of art. Indeed, this prolific artist, jeweler in its infancy then miniaturist, engraver, painter and muralist, has to be a certain age, with critics, historians, writers, artists, and photographers. Then there has been an oversight, and finally a gradual renaissance. Here is a focus on a particular face of Marcel-Lenoir: that of fresco. Marcel-Lenoir, from jewel to fresco, his name is at the heart of the revival of sacred art and the resurrection of the fresco. In 1920, he founded the Institute of contemporary aesthetics in his workshop, 115, rue Notre-Dame-des-Champs, for teaching the fresco, where he receives many French and foreign students. Surrounded by some of them, he made between 1920 and 1923 for the Catholic Institute of Toulouse a monumental fresco of 90 square meters celebrated in the world of art: The Coronation of the Virgin. This is included in the supplementary inventory of historical monuments since February 13, 1996. In addition, the fresco knew at the time a certain notoriety thanks to the success generated by the Annunciation, preserved in the church of Montricoux. Finally, he worked on other projects of frescoes, large and small, little known, destroyed, incomplete, fallen into oblivion, as the Red Ribbon Woman stored in the reserves of the Musée National d’Art Moderne, Centre Georges Pompidou. In his paintings, Marcel-Lenoir, Rider of ideal communion is human and divine. As an independent man, guided by his religion aesthetics, he left then a personal work, modern, distinguished among all the assets dedicated to the fresco.